DICIPLINE MANAGEMENT STRATEGY - Sakban; Rika Aryani (JURNAL ISLAMIKA, 2020)
ABSTRAK In a organization, good of education organization and also other organization, human resource represent central factor and very required by a[n organization. Without existence of human resource, organizational will not mean something. Therefore, human resource require to be managed by professional so that organization can expand productively, and employees can work better. Employees performance influenced by various factor, for example: activity environment, leadership, activity motivation, as well as activity discipline. Activity discipline represent conscious attitude or readiness a employees to do and adhere specified orders. Employees with activity discipline which is good to be expected can execute and finish work becoming its responsibility effectively and efficient and also on time. As for discipline management strategy shall be as follows 1) its clear Decision formula, its sensible order, publicized, and run neglectlessly 2) Its fair execution by using enunciated law and commemoration 3) Leadership of accomodated supervision at discipline orders 4) uniform and fair execution. Keyword: Strategy Management, Management, Management Discipline